The economic valuation of the environment and public policy : a hedonic approach - Hidano, Noboru (Cheltenham, U.K. ; Northhampton, Mass., U.S. : E. Elgar Pub., 2002)
This text is especially designed to illustrate the basic assumptions of the hedonic approach and highlight the strengths and weaknesses associated with it. Combining rigorous theoretical analysis, detailed empirical studies and an extensive history of hedonic valuation, the book is both an introduction to the field and an aid for professionals and practitioners. It includes: a comprehensive explanation of the basic theorem; extensive discussions on the utility.
Includes bibliographical references (p. 154-161) and index.
oif 05/08/16
Loan
Keywords: Environmental economics; Hedonism; Environmental policy